2009
DOI: 10.1001/jama.2009.681
|View full text |Cite
|
Sign up to set email alerts
|

Cardiorespiratory Fitness as a Quantitative Predictor of All-Cause Mortality and Cardiovascular Events in Healthy Men and Women

Abstract: ORONARY HEART DISEASE (CHD) is a major cause of disability and premature death throughout the world. 1 Epidemiological studies have demonstrated an inverse association between physical fitness and the incidence of CHD or allcause mortality in healthy or asymptomatic participants. Physical fitness is typically expressed as cardiorespiratory fitness (CRF) and is assessed by exercise tolerance testing 2 ; however, it is rare for clinicians to consider CRF when evaluating future risk of CHD. 3 A major reason for l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

76
1,925
5
109

Year Published

2010
2010
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 2,608 publications
(2,115 citation statements)
references
References 63 publications
76
1,925
5
109
Order By: Relevance
“…Among participants with ≥2 metabolic risk factors at baseline, those who reported engaging in moderate‐to‐vigorous physical activity ≥3 times per week had an HR for CVD mortality of 0.63 (95% CI, 0.40–0.99) compared with those who reported none. Similar findings have been reported in a few other cohort studies for physical activity23, 24, 25 as well as for physical fitness 26. In a meta‐analysis examining cardiorespiratory fitness as a predictor of all‐cause mortality and CHD/CVD, results from 8 cohort studies indicated that each MET higher level of maximal aerobic capacity correlated with an 11% (95% CI, 7%–15%) lower risk of CHD/CVD among individuals with >3 metabolic factors 26…”
Section: Discussionsupporting
confidence: 82%
“…Among participants with ≥2 metabolic risk factors at baseline, those who reported engaging in moderate‐to‐vigorous physical activity ≥3 times per week had an HR for CVD mortality of 0.63 (95% CI, 0.40–0.99) compared with those who reported none. Similar findings have been reported in a few other cohort studies for physical activity23, 24, 25 as well as for physical fitness 26. In a meta‐analysis examining cardiorespiratory fitness as a predictor of all‐cause mortality and CHD/CVD, results from 8 cohort studies indicated that each MET higher level of maximal aerobic capacity correlated with an 11% (95% CI, 7%–15%) lower risk of CHD/CVD among individuals with >3 metabolic factors 26…”
Section: Discussionsupporting
confidence: 82%
“…Sustaining regular physical activity over the long term is associated with a more favorable circulating metabolome19 and decreased markers of inflammation 20. Benefits of cardiorespiratory fitness may extend to non‐CVD diseases, such as cancer, depression, and dementia, with a dose‐dependent reduction in all‐cause mortality 21, 22, 23, 24…”
Section: Discussionmentioning
confidence: 99%
“…The proportion of adolescents in this study with low cardiorespiratory fitness may be a reflection of lower cardiorespiratory fitness levels observed worldwide. These data are alarming considering the exposure of young individuals to cardiovascular risk factors during adolescence7 and adulthood 8…”
Section: Discussionmentioning
confidence: 99%
“…The low level of cardiorespiratory fitness is associated with increased cardiovascular risk factors and metabolic syndrome in young individuals,7 as well as to increased cardiovascular risk in adulthood 8. A meta-analysis showed that the overall risk of death from all causes or from cardiovascular disease was two-fold higher in individuals with low cardiorespiratory fitness levels, compared to those with high levels 8.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation